UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA MAPEL FIQIH MELALUI METODE COOPERATIVE TIPE PICTURE AND PICTURE - RATU SUMIYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
There is a tendency in education today to fall back on the idea that children will learn better if the environment is created naturally. Learning will be more meaningful if children